Faktor-faktor yang Mempengaruhi Minat Berkarir di Bidang Perpajakan dengan Penghargaan Finansial Sebagai Moderasi - Valda Shakila; Desi Ika (Forum Kerjasama Pendidikan Tinggi, 2025)
This study aims to examine the influence of tax literacy, motivation and job market considerations on accounting students' interest in a career in taxation with financial rewards as moderation. This study uses a quantitative approach, with primary data obtained from the distribution of questionnaires to accounting students in a number of universities in Medan with purposive sampling and as many as 185 respondents will be sampled. The analysis techniques used are multiple linear regression and moderation test with an absolute difference uses SPSS 26.The results showed that tax literacy had no effect on accounting students' interest in a career in taxation having a significant result of 0.063, while motivation and job market considerations had an influence on accounting students' interest in a career in taxation which had significant results of 0.000 and 0.002. Financial rewards are not able to moderate the relationship between tax literacy had a significant result of 0.243, but effectively moderated motivation and job market considerations on accounting students' interest a career in taxation. had significant results of 0.010 and 0.032, respectively.